2005
DOI: 10.1111/j.1601-0825.2005.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of dentists in Jordan to treat HIV‐infected patients

Abstract: Present data suggest that HIV-infected individuals will have difficulty in obtaining dental health care in Jordan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
3
36
1
2
Order By: Relevance
“…Although these results are in agreement with some published reports [12,19], the willingness of treating HIV/AIDS patients is, however, felt an over optimistic by enthusiastic students in this conservative society where AIDS is still in low prevalence rates. A study conducted in Jordan few years ago to investigate willingness of working dentists to treat HIV infected patients has shown that, when a fake AIDS patient contacted dental practices by phone for treatment of pain of dental origin, there was fear of the HIV illness and only 15% accepted to provide such treatment [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Although these results are in agreement with some published reports [12,19], the willingness of treating HIV/AIDS patients is, however, felt an over optimistic by enthusiastic students in this conservative society where AIDS is still in low prevalence rates. A study conducted in Jordan few years ago to investigate willingness of working dentists to treat HIV infected patients has shown that, when a fake AIDS patient contacted dental practices by phone for treatment of pain of dental origin, there was fear of the HIV illness and only 15% accepted to provide such treatment [20]. …”
Section: Discussionmentioning
confidence: 99%
“…[1718] In the studies conducted in various countries,[17181920] although satisfactory knowledge level among the study participants was there, a stigma was reported regarding the treatment of HIV/AIDS patients. Studies done in South Africa, Brazil, Japan, and Sudan demonstrated that dental students had insufficient knowledge regarding HIV, its mode of transmission, and management of HIV positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in oral health of HIV positive individuals has been reported to be significantly associated with improvements in both physical and mental health 13 . Although reasonable numbers of oral health care practitioners in some parts of the world remain unwilling to render care to this patient group 14,15 . Majority of Nigerian dentist (93%) reported willingness to treat HIV infected patients while observing universal precautions 16 .…”
Section: Introductionmentioning
confidence: 99%